(untitled) (Nigerian Journal of Technology, 2017)
This study investigated the soil bearing capacity and foundation settlement characteristics of Minna City Centre development site using standard penetration test (SPT) data obtained from10 SPT boreholes at 0.6, 2.1 and 3.6 m depths to correlate soil properties. Evaluation of foundation bearing capacity and settlement characteristics for geotechnical preliminary design of foundations was carried out using some conventional empirical/analytical models and numerical modelling. The aim was to investigate and determine the geotechnical parameters required for adequate design of Physical structures of the proposed Minna City Centre, at Minna the capital of Niger state. The SPT N-values were corrected to the standard average energy of 60% (N60) before the soil properties were evaluated. Using the corrected N-values, allowable bearing pressure and elastic settlement of shallow foundations were predicted at 50 kN/m2 applied foundation pressure. The numerical analysis results using Plaxis 2D, a finite element code, shows the analytical/empirical methods of estimating the allowable bearing pressure and settlements of shallow foundations that provided acceptable results. Results obtained show that an average bearing capacity value of 100 – 250 kN/m2 can be used for shallow foundations with embedment of 0.6 to 3.6 m on the site. http://dx.doi.org/10.4314/njt.v36i3.1